THE IDENTIFICATION OF BACTERIAL SYMBIONT’S OF THE LARVAE ORYCTES RHINOCEROS L. AND THE ROLE OF THE BACTERIA IN COMPOSTING PROCESS - Sijabat, Octanina Sari; Marheni, Marheni; Bakti, Darma (Journal of Community Research and Service, 2017)
AbstractOryctes rhinoceros L. has symbioses with micro organisms in their hind guts which further break down plant material consumed by beetle. The aim of this research is to determine the identification of the existence of the bacterial species in the hind gut larvae of the symbiotic bacteria using biochemical test and analysis based on 16S rRNA. The result of this research indicate that there were two different bacterials: Bacillus siamensis and Bacillus stratosphericus found. The bacteria was used for starting the composting and more specifically, the Bacillus siamensis can speed up composting with the end result at C/N 13.16.Keywords: Larvae O. rhinoceros L, Bacterial Symbionts, 16S rDNA, Composting